2011
DOI: 10.1258/ebm.2011.010307
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis reveals the active roles of keratinocytes in oral mucosal adaptive immune response

Abstract: To elucidate the roles of oral keratinocytes in the adaptive immune response of oral mucosa, global gene expression analysis was performed by microarray technique and integrating computational methods, including hierarchical clustering, biological process Gene Ontology analysis, Kyoto Encyclopedia of Genes and Genomes pathway analysis, self-organizing maps (SOMs) and biological association network analysis (BAN). Raw data from microarray experiments were uploaded to the Gene Expression Omnibus Database, http:/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
0
11
2
Order By: Relevance
“…The details of the protein isolation and western blot analysis have been described in a previous study 31 . A specific anti-human IL-1β antibody (1:1000), an anti-human β-actin antibody (1:1000) from Cell Signaling Technology (Danvers, MA, USA) and horseradish peroxidase conjugated goat secondary antibodies (Beyotime Institute of Biotechnology, Haimen, Jiangshu China) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the protein isolation and western blot analysis have been described in a previous study 31 . A specific anti-human IL-1β antibody (1:1000), an anti-human β-actin antibody (1:1000) from Cell Signaling Technology (Danvers, MA, USA) and horseradish peroxidase conjugated goat secondary antibodies (Beyotime Institute of Biotechnology, Haimen, Jiangshu China) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The microarray data were processed and analyzed as described previously 31 . A differentially expressed gene was defined as a variation in gene expression no less than 2-fold or 1.5-fold with a detection P value of less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many details underlying effect of TSLP on cacinogenesis such as signal transduction mechanisms are largely unknown. Our previous study found that TSLP was expressed on mouse oral keratinocyte under inflammation [29], and TSLP and its receptor were detected on oral squamous cell carcinoma cell line (unpublished data). Whether TSLP is also involved in the carcinogenesis in other epithelial tumor type which progression have been reported to be associated with immune disregulation and elevated Th2 cytokines expression such as head and neck carcinoma remains to be fully elucidated in further study [30,31].…”
Section: Perspectivementioning
confidence: 81%
“…Very interestingly, the top biological function in both upregulated gene clusters Up-II and Up-III was the biological process of skin development. Among a total of 32 genes identified (9 + 23; Table 1), 28 genes (the exceptions being Prdm1 , Calml5 (calmodulin-like 5), Foxe1 (forkhead box E1), and Tfap2a (transcription factor AP-2 alpha)) were also found to be expressed in normal differentiated keratinocytes in mouse oral mucosa [53], the gene expression data of which were obtained from GEO, an accession number of GSE28035. In these genes, it has been reported that Evpl (envoplakin) [35], Scel (sciellin) [4], Tgm1 [8], and Tgm3 [56] are involved in the development of epidermis.…”
Section: Discussionmentioning
confidence: 99%